Association between short interpregnancy interval and placenta accreta spectrumAJOG Global Reports at a Glance - Hannah D. McLaughlin, MD; Ashley E. Benson, MD; Morgan A. Scaglione, MD; Jane S. Saviers-Steiger, BS; Dana R. Canfield, MD; Michelle P. Debbink, MD, PhD; Robert M. Silver, MD; Brett D. Einerson, MD (Elsevier, 2022)
BACKGROUND: The incidence of placenta accreta spectrum is increasing in parallel with the growing number of cesarean deliveries performed. A shorter interpregnancy interval following cesarean delivery may prevent adequate scar healing, which could impact the risk of placenta accreta spectrum. OBJECTIVE: We aimed to investigate the association between short interpregnancy intervals and placenta accreta spectrum. STUDY DESIGN: We conducted a retrospective cohort study of patients at risk for placenta accreta spectrum at a tertiary academic center between 2002 and 2020. Our cohort was defined as pregnant individuals at risk for placenta accreta spectrum meeting the following criteria: placenta previa with previous cesarean delivery and/or uterine surgery, anterior low-lying placenta with previous cesarean delivery and/or uterine surgery, ≥3 previous cesarean deliveries, or any previous cesarean delivery with sonographic findings suspicious for placenta accreta spectrum. The primary outcome was surgically or histopathologically confirmed placenta accreta spectrum. Short interpregnancy interval was defined as <18 completed months from previous delivery and last menstrual period of the index pregnancy. Univariable analyses were performed with chi-square and Student's t-test, as appropriate, and Kruskal-Wallis for nonparametric variables. The unadjusted and adjusted odds ratios were calculated using multivariate logistic regression models. Covariates were selected if P<.2 in univariable analyses or defined a priori as clinically meaningful. The final models were derived using reverse stepwise selection of variables. We used Stata Statistical Software, version 15 (StataCorp, College Station, TX) to perform descriptive statistics. RESULTS: Of 262 patients at risk of placenta accreta spectrum with complete records, 112 (42.7%) had placenta accreta spectrum. Pregnant individuals with short interpregnancy intervals of <18 months were no more likely than those with optimal interpregnancy intervals to have previa (58% [46/80] vs 46% [84/182]; P=.09) or placenta accreta spectrum (49% [39/80] vs 40% [73/182]; P=.19). Short interpregnancy interval of <18 months was not associated with placenta accreta spectrum (unadjusted odds ratio, 1.06; 95% confidence interval, 0.62-1.80). This association did not change when adjusting for previa and number of previous cesarean deliveries (adjusted odds ratio, 1.04; 95% confidence interval, 0.51-2.15). In a secondary analysis, an interpregnancy interval of <12 months was also not associated with placenta accreta spectrum (unadjusted odds ratio, 0.79; 95% confidence interval, 0.04-1.56; adjusted odds ratio, 0.52; 95% confidence interval, 0.21-1.27). CONCLUSION: In patients at risk for placenta accreta spectrum, short interpregnancy intervals of <18 months or <12 months were not associated with placenta accreta spectrum, even when controlling for number of previous cesarean deliveries and previa. Short interpregnancy interval is not likely to be an important modifiable independent risk factor for placenta accreta spectrum.